The Effect of Ratio of Tapioca and Taro Flour with Addition of Arabic Gum on the Quality of Spinach Nugget - Friscillia Anggia Rizki; Herla Rusmarilin; Sentosa Ginting (Jurnal Rekayasa Pangan dan Pertanian, 2014)
The aim of this research was to  find the effect of  the ratio of  tapioca and taro flour with addition of arabic gum on the quality of spinach  nugget. The research was using completely randomized design with two factors, i.e  ratio of tapioca and taro flour (T): (20%:80%, 40%:60%, 60%:40%, and 80%:20%) and concentration of  arabic gum  (G) : (0,25%, 0,50%, 0,75%, and 1%). Parameters analyzed  were moisture content, ash content, protein content, fat content, crude fiber content, organoleptic value of  flavor, taste, and texture. The results showed that the ratio of  tapioca and taro flour had highly significant effect on moisture content, ash content, fat content, protein content, crude fiber content, organoleptic value of  taste, and texture. The concentration of  arabic gum  had highly significant effect on moisture content, ash content, protein content, crude fiber content, organoleptic value of  taste, and texture. Interaction of the two factors had significant effect on moisture content and ash content. The ratio of tapioca and taro flour of 20%:80% and concentration of  arabic gum 1% produced the best spinach nugget. Keywords: Arabic Gum, Nugget, Spinach, Tapioca, Taro Flour